Regulation of K+ Nutrition in Plants - Ragel, Paula; Raddatz, Natalia; Leidi, Eduardo O.; Quintero, Francisco J.; Pardo, José M. (Frontiers in Plant Science, 2019)
Modern agriculture relies on mineral fertilization. Unlike other major macronutrients, potassium (K+) is not incorporated into organic matter but remains as soluble ion in the cell sap contributing up to 10% of the dry organic matter. Consequently, K+ constitutes a chief osmoticum to drive cellular expansion and organ movements, such as stomata aperture. Moreover, K+ transport is critical for the control of cytoplasmic and luminal pH in endosomes, regulation of membrane potential, and enzyme activity. Not surprisingly, plants have evolved a large ensemble of K+ transporters with defined functions in nutrient uptake by roots, storage in vacuoles, and ion translocation between tissues and organs. This review describes critical transport proteins governing K+ nutrition, their regulation and coordinated activity, and summarizes our current understanding of signaling pathways activated by K+ starvation.